Bibliometric Analysis of 50 Most Cited Articles on Odontomas - Gozde Serindere; Mehmet Serindere (Association of Support to Oral Health Research (APESB), 2022)
Objective: To identify the citation features and review articles on odontomas using bibliometric analysis. Material and Methods: A list of studies about odontoma was obtained by searching using the Scopus database. Abstracts or full texts were read and evaluated. After then, 50 most cited articles were achieved. Studies were categorized as citation numbers, citation density, journal name, article type, the affiliation of the first author and publication year. Descriptive statistics were used to analyze the results. Results: The most frequently cited article received 358 citations, while the least frequently cited article received 42 with a mean of 94.3 citations per article. The mean citation density was 5.13. The study with the highest citation density (12.31) was published in 2006. The highest citation number was found in the 2000s following the 1990s. The 50 most cited articles were published from 1971 to 2011, with 84% (42 of 50) published after 1990. USA (n = 9) and Brazil (n = 6) were the two most contributing countries. According to article type, there were eight (16%) review articles. Conclusion: The USA found to have a strong influence on research about odontoma, followed by Brazil. All researches were reported in English, and most of them were published in good quality journals.